Echoes of Exclusion and Resistance : Voices from the Hanford Region - Franklin, Robert R., 1981-; Bauman, Robert, 1964- (Book collections on Project MUSE., 2020)
"Four scholars draw from oral histories to focus on experiences of non-white groups such as the Wanapum, Chinese immigrants, interned Japanese Americans, and African American migrant workers, whose lives were deeply impacted by the Hanford Site. Each group resisted segregation and discrimination, and in the process, challenged the region's dominant racial norms"--